Impact of outdated CQI report on adapted well-known packet scheduling algorithm when streaming video - Mohd. Ramli, Huda Adibah; Mohd. Isa, Farah Nadia; Ismail, Ahmad Fadzil; Hasan, Muhamad Kamrul; Hashim, Wahidah (IEEE Computer Society, 2015)
Given that there are overgrowing demands for video streaming application in the downlink Long Term Evolution Advanced (LTE-A), effective scheduling of these delay-sensitive real-time packets are critical. However, there remains a challenge where (re)transmission of video packets in the downlink LTE-A may subject to numerous impairments including outdated Channel Quality Information (CQI) report. This paper studies the impact of outdated CQI on the adapted Maximum-Largest Weighted Delay First Performance (M-LWDF) namely Adapted M-LWDF1 (AM1) and Adapted M-LWDF2 (AM2) algorithms. Note that the AM1 algorithm chooses a user first then (re)transmit packets to the selected user on the best mobile cellular channels whereas scheduling decision in AM2 algorithm is made on per mobile cellular channel basis. Simulation results demonstrate the robustness of the AM2 algorithm in minimizing the detrimental effects due to outdated CQI report when streaming video